Association of Smoking with Indicators of the Structure and Function of Blood Vessels in Middle-aged Men - O. Yu. Isaykina (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2020)
Aim. To study the association of smoking with indicators of the structure and function of blood vessels in a sample of middle-aged men.Material and methods. This study is part of a 32-year prospective cohort observation of males starting in childhood (11-12 years). The study included 301 (30.0%) representatives of the original population sample aged 41-44 years. The examination included a survey on a standard questionnaire with an assessment of the status and intensity of smoking, of anthropometric indicators, blood pressure (BP), and determination of the blood lipid spectrum. The stiffness of the arterial wall and central pressure were measured by the method of applanation tonometry. The carotid intima-media thickness of the common carotid artery (C-IMT) was estimated by the method of ultrasonic duplex scanning of the main vessels of the neck.Results. Of the 301 men examined, aged 41-44 years, 92 (30.6%) people never smoked, 73 (24.3%) smoked in the past and 136 (45.2%) people currently smoke. Former smokers were divided by the intensity of smoking in the past as follows: less than 20 cigarettes/day were smoked by 41 (56.0%) people, and ≥20 cigarettes/day - 32 (44.0%) people. Among current smokers, less than 20 cigarettes/day were smoked by 63 (46.0%) people, and ≥20 cigarettes - 73 (54.0%) people. Current smokers have a statistically significantly higher level of triglycerides and lower cholesterol of high density lipoproteins in the blood, augmentation index (AIx), augmentation blood pressure and C-IMT thicker than non-smokers. The thickness of the C-IMT and AIx was statistically significantly greater among current smokers who smoked 20 or more cigarettes daily. Men who smoked in the past had significantly greater body weight, waist circumference and pulse wave velocity. 12.4% of AIx variability was attributable to current smoking combined with variability in alcohol consumption, blood glucose, and heart rate. The body mass index (BMI) and ethanol consumption are independent determinants of peripheral and central systolic pressure, and account for 17.8% and 18.6% of their variance, respectively. The combined contribution of current smoking, age, BMI, low-density lipoprotein cholesterol and plasma glucose to the thickness variability of C-IMT was 13.7%. Among men with a smoking duration in the past >10 years, the levels of total cholesterol, triglycerides and arterial stiffness indicators - AIx, pulse pressure amplification were higher compared to peers with a shorter smoking duration.Conclusion. Current smoking is associated with atherogenic changes in the blood lipid spectrum, impaired structure and function of the main arteries. Moreover, the severity of structural and functional disorders of the arteries is associated with the intensity of current smoking. If you give up smoking, there is a potential possibility of reversibility of these vascular disorders.